2011
DOI: 10.2217/iim.11.62
|View full text |Cite
|
Sign up to set email alerts
|

3D optical coherence tomography for clinical diagnosis of nonmelanoma skin cancers

Abstract: High-resolution frequency domain optical coherence tomography (OCT) stands out amongst a range of novel dermatologic imaging technologies, with its good detection sensitivity around -100 dB, high measurement speeds allowing real-time image acquisition and its ability to acquire high definition crosssectional and 3D tomograms of regions greater than 1 cm 2 , providing tissue information comparable to conventional histopathology without the need for any contrast agents. Typical axial and transverse resolutions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 86 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…(b) and (c) 2 × 2 mm en-face mean projection over depth range indicated in (a) of the fly through the microvasculature starting from surface (). Scale bars indicate 250 µm in every picture. is a representative tomogram of the referred location visualizing the characteristic layers of a glabrous skin [21]. The stratum disjunctum (SD) appears as a first thin bright layer.…”
Section: Resultsmentioning
confidence: 99%
“…(b) and (c) 2 × 2 mm en-face mean projection over depth range indicated in (a) of the fly through the microvasculature starting from surface (). Scale bars indicate 250 µm in every picture. is a representative tomogram of the referred location visualizing the characteristic layers of a glabrous skin [21]. The stratum disjunctum (SD) appears as a first thin bright layer.…”
Section: Resultsmentioning
confidence: 99%
“…The most characteristic feature of a nodular BCC in MPT was peripheral palisading of basal cells around the tumor cell nests [47]. Meanwhile, BCC displayed features such as plug-like signal intense structures and signal-free cavities in OCT [20,48]. Melanoma was characterized in MPT by features such as large intercellular distances, pleomorphic cells and the presence of dendritic cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal combinations of several non-invasive imaging modalities suitable for dermatological applications have been investigated [20,43]. In an ex vivo study, MPT/fluorescence lifetime imaging (FLIM) approach has been shown to be useful for demarcating malignant melanoma and BCC [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the noninvasive skin cancer diagnostics the application of biomedical imaging is known, such as PET [4], optical coherence tomography [5,6], confocal microscopy [7]. However, the imaging methods are labour-consuming and expensive, and their application is reasonable for updating the already established diagnosis, planning and control of the treatment process.…”
Section: Introductionmentioning
confidence: 99%